2021
DOI: 10.1021/acsomega.1c00818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Concentration and the Type of Dispersant on the Synthesis of Copper Oxide Nanoparticles and Their Potential Antimicrobial Applications

Abstract: The bactericidal properties of copper oxide nanoparticles have growing interest due to potential application in the medical area. The present research investigates the influence of sodium dodecyl sulfate (SDS) and poly­(vinylpyrrolidone) (PVP) on the production of copper oxide nanoparticles prepared from copper sulfate (CuSO4) and sodium borohydride (NaBH4) solutions. Different analytical techniques were used to determine the crystal nature, mean size diameter, and surface morphology of the copper oxide nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 81 publications
3
8
0
Order By: Relevance
“…For E. coli, more CuO nanoparticles concentration was required to inhibit the bacteria. Similar results were reported by Guzman et al [21], where they observed that CuO nanoparticles with particle size range of 4.1 ± 1.9 nm were more effective in inhibiting both S. aureus and E. coli, with the results being more pronounced to S. aureus. From the above studies, it is not conclusive why the CuO nanoparticles are better in inactivating gram positive bacteria with higher activity compared to gram negative bacteria.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…For E. coli, more CuO nanoparticles concentration was required to inhibit the bacteria. Similar results were reported by Guzman et al [21], where they observed that CuO nanoparticles with particle size range of 4.1 ± 1.9 nm were more effective in inhibiting both S. aureus and E. coli, with the results being more pronounced to S. aureus. From the above studies, it is not conclusive why the CuO nanoparticles are better in inactivating gram positive bacteria with higher activity compared to gram negative bacteria.…”
supporting
confidence: 90%
“…It is widely acknowledged that the higher the surface area per unit mass, the more active and effective the material becomes. In addition to the surface characteristics of the material, the release of ions plays a major role [19,21,53]. The exact bacterial mechanism of CuO nanoparticles is still not yet fully understood, it emerges that several mechanisms have been suggested which include (1) the immediate interaction of CuO nanoparticles and bacterial surfaces, consequently damaging the cell wall of the bacteria.…”
Section: Antibacterial Activity Of Cuo Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified chemical reduction method proposed by Badawy et al [ 54 ] was used for the synthesis of Cu 2 O Nps [ 55 , 56 ]. For the synthesis, ethanolic solutions of sodium hydroxide (20 mM), Mg nitrate (20 mM), Mn nitrate (20 mM) and La nitrate (20 mM) were used.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that the addition of dispersant does not achieve the expected effect and does not optimize the formation of the product, which may be related to many factors such as the amount of dispersant used, the amount of OH À in the solution, and the amount of Cu 2+ loaded on the resin. 28 In later research, the systematic experiments and the detailed analysis will be conducted.…”
Section: Characterization Of Semmentioning
confidence: 99%